European disintegration: Too much to lose - Bettina Rudloff; Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2016)
For decades the search for deeper integration characterised the European Union. Today the discussion revolves around disintegration. It began with the Greek debt crisis, but only came into its own with summer 2015's major influx of refugees and the reimposition of controls at certain borders. In June the United Kingdom will vote on whether to remain in the EU. In April, Dutch voters expressed their criticism of the EU through their referendum on the Association Agreement with the Ukraine, which may hinder its ratification. These developments are generating uncertainty over the Union's future. Closer examination of the common trade policy and the single market, as one of the central pillars of European integration, reveals that all member-states would have a great deal to lose if the Union were to break apart. (SWP Comments)
Keywords: 320